Discussing Adaptive Approaches for Development Programmes - Pett, Jamie (Medium - LearnAdapt, 2020)
What can adaptive approaches from other sectors teach development practitioners about dealing with uncertainty?

A Guide To Agile Project Management Methodology & Tools - Aston, Ben (The Digital Project Manager, 2020)
Looking to brush-up on agile? Here's your complete guide to agile project management, agile principles and key components, and the best agile tools for 2020.

Four ways development practitioners can borrow from private sector adaptive approaches - Pett, Jamie (LearnAdapt, 2020)
Agile, lean startup and human-centred design can be an answer — if you’re asking the right questions

Navigating adaptive approaches for development programmes - Pett, Jamie (ODI, 2020)
This working paper compares six of the most prominent adaptive approaches to emerge over the past two decades. Three come from the world of innovation, largely in the private sector (agile, lean startup and human-centred design), and three from the global development sector (thinking and working politically, forms of adaptive management and problem-driven iterative adaptation). While all of these approaches are valuable when used in the right context, practitioners may be perplexed by the multiplicity of methods and jargon. This paper aims to address some of this confusion by mapping where these approaches have come from and showing how they can be applied across the adaptive programme cycle. Armed with this knowledge, practitioners might experiment with different combinations and sequences of adaptive approaches according to the kind of problem and context faced. In turn, this may help us move beyond a siloed view of approaches linked to innovation, adaptive management or more politically smart ways of working. Key messages: • Adaptive approaches have emerged in several sectors, including software development, product and service design, technology startups and international development. • Adaptive approaches can help practitioners counteract misplaced certainty. By talking to potential users, understanding institutions, interests and ideas and investigating the root causes of a problem, practitioners applying these approaches can illuminate the underlying nature of the problem and context. • Rather than building a whole solution straight away, these approaches commonly encourage practitioners to start small and use structured cycles of testing and learning. There is scope to further consider how different approaches can be better brought together and combined. • Adaptive approaches in development provide a wider range of options for what to create and facilitate – not only products or services, but also forms of collective action. There are also alternative ways to think about scale – considering how others might take up an idea and looking for leverage, rather than quantity.

Software Engineering at Google: Lessons Learned from Programming Over Time - Winters, Titus; Manshreck, Tom; Wright, Hyrum (O'Reilly Media, 2020)
Today, software engineers need to know not only how to program effectively but also how to develop proper engineering practices to make their codebase sustainable and healthy. This book emphasizes this difference between programming and software engineering. How can software engineers manage a living codebase that evolves and responds to changing requirements and demands over the length of its life? Based on their experience at Google, software engineers Titus Winters and Hyrum Wright, along with technical writer Tom Manshreck, present a candid and insightful look at how some of the world's leading practitioners construct and maintain software. This book covers Google's unique engineering culture, processes, and tools and how these aspects contribute to the effectiveness of an engineering organization. You'll explore three fundamental principles that software organizations should keep in mind when designing, architecting, writing, and maintaining code: How time affects the sustainability of software and how to make your code resilient over time How scale affects the viability of software practices within an engineering organization What trade-offs a typical engineer needs to make when evaluating design and development decisions

A new bird's eye view on the agile forest - Portman, Henny (PM World Journal, 2020)

Chaos Report 2020 - Standish Group (Standish Group, 2020)